2012
DOI: 10.1111/j.1600-9657.2012.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries in primary school children of South India – a report from district‐wide oral health survey

Abstract: The findings of this study show that dental trauma has a moderately high prevalence among Indian primary school children. Community, especially parents and school teachers, should be educated about prevention and early management of dental trauma in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
3
23
0
8
Order By: Relevance
“…Similar to earlier studies in Sweden and other countries (13,29,30), falling was found to be the most common cause of dental trauma. Similar to earlier studies in Sweden and other countries (13,29,30), falling was found to be the most common cause of dental trauma.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to earlier studies in Sweden and other countries (13,29,30), falling was found to be the most common cause of dental trauma. Similar to earlier studies in Sweden and other countries (13,29,30), falling was found to be the most common cause of dental trauma.…”
Section: Discussionsupporting
confidence: 88%
“…El porcentaje de ocurrencia de este fenómeno es semejante al de otros países como Brasil o, incluso, al de algunos otros estudios reportados en Colombia. Si se compara la frecuencia de este incidente respecto al sexo de los pacientes atendidos, hay predominio del sexo femenino; situación diferente a las investigaciones realizadas en Recife (Brasil) [14], en la Clínica Universitaria de Alemania [21] y en el Sur de India [22], que indica mayor trauma dentoalveolar en hombres. Otro hallazgo diferente a nuestro estudio es la edad en la cual ocurre el incidente; mientras en diversos estudios se presenta con mayor frecuencia en edades tempranas [3,6,9,14,[21][22][23], nuestros resultados informan edades superiores a los 40 años.…”
Section: Discusión De Resultadosunclassified
“…No obstante, también se encuentran similitudes en varios de los estudios consultados [2,8,[21][22][23][24] con respecto al motivo del trauma dentoalveolar, lo cual indica que la principal causa son los impactos directos por caídas, seguida de los accidentes automovilísticos, además del uso inadecuado de los dientes frente a objetos duros a la hora de la alimentación o simplemente asociados a hábitos [5].…”
Section: Discusión De Resultadosunclassified
See 2 more Smart Citations